Thyrotropinoma and multinodular goiter: A diagnostic challenge for hyperthyroidism - Duygu Yazgan Aksoy; Arzu Gedik; Nese Cinar; Figen Soylemezoglu; Mustafa Berker; Omer Alper Gurlek (Journal of Research in Medical Sciences, 2013)
Thyroid disorders are frequently encountered. The diagnosis is straightforward unless clinical or laboratory findings are inconclusive and/or perplexing. Hyperthyroidism due to a thyrotropin-secreting pituitary adenoma rarely occurs and symptoms due to thyroid hormone excess are subtle. The presentation of the disease becomes unusual when co-secretion of other hormones with thyrotropin or concomitant thyroid parenchymal pathology exist. We present the case of a 63-year-old female patient with thyrotropinoma co-secreting growth hormone and multinodular goiter. She developed hyperthyroidism first due to thyrotropinoma and later due to a toxic nodule. Herein, we discuss the diagnostic and therapeutic challenges of hyperthyroidism with atypical presentation.